Northwest history. Mining. Roads & trails. 1937-11-20 (1937)
Forest road will aid in shipment of ores<br. Mike Savage has a contract with the forest service to build a seven mile section of road that will connect the Jack Waite mine with the Beaver creek road. This will make the shipping point at Belknap easier of access for the Jack Waite mine.